Diglossia of Javanese-Indonesia in Senior High School Educational Domain: Sociolinguistics Study in Tegal Regency - Saddiyah, Chalimatus; Rokhman, Fathur (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2018)
Tegal regency people is diglossic community having two languages namely Javanese and Indonesian. The adjustments of the role and the function of those languages are occured in the city, especially in Senior High School educational domain, taking form of the roles and functions of Javanese and Indonesian languages. The purposes of the research are to analyze the patternof Javanese-Indonesian language diglossic patterns in Tegal SHS educational domains. The research is descriptive qualitative and perspective sociolinguistics. The data collection uses observe and conversational methods. The diglossia of the domain uses Miles and Huberman, covering data collection, data reduction, then data serving and concluding. Based on analysis, the diglossic patters of the domain are: (1) Standardized Indonesian language and Javanese language are included in high language variation used in formal situation, and (2) non-standardized Indonesian and Javanese languages are used in non-formal situations and included in low language variation.